Statistic estimation of participation of the ukrainian economy in global economic connections - Кущенко, Ірина; Мамонтова, Ольга (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article considers statistic indexes used to define the involvement of different countries in the world economic system. We suggest methods for index calculation of relative export specialization and diversification which can be used to show statistic estimation of regional involvement into outereconomic connections of the Ukraine.